Awareness and Attitude towards Vasectomy among Married Men of a Selected Community - Rijal, Manisa; Thapa, Babita; Rayamajhi, Anju (Journal of Advanced Academic Research, 2024)
Background: Vasectomy is one of the safest and most effective family planning methods and is one of the few contraceptive options available for men. It is a surgical procedure performed on males in which the vas deferens are cut, tied, cauterized or interrupted to induce sterility. It is one of the least used contraceptive methods in the developing world including Nepal despite its lots of benefits. The objective of the study was to find out the awareness and attitude of married men towards vasectomy. Methods: A descriptive cross-sectional research design was adopted to assess the level of awareness and attitude towards vasectomy among 96 married men having at least one child in Birendranagar Municipality, ward number 3 of Surkhet district. Data was collected by using the purposive sampling technique. A semi-structured interview schedule was used in community setting to collect data. Collected data were analyzed by using both descriptive and inferential statistics. Results: Total 96 married men participated in the study. Among them, 53.1% of the respondents had moderate awareness level, 38.5% of the respondents had inadequate awareness level and only 8.3% of the respondents had high awareness level. Most (86.5%) of the respondents had positive attitude and 13.5% had negative attitude towards the vasectomy. There was association between level of awareness with educational status of the respondents (p=0.024). Conclusion: The study concludes that the men of Birendranagar Municipality are moderately aware about vasectomy. So, it is necessary to enhance awareness on vasectomy by launching awareness programme through different mass media with valid information.